La terminología de la danza clásica en el aula: la webquest como actividad didáctica - Barri Almenar, Ana (Anales de Filología Francesa, 2010)
The process of teaching / learning the terminology of classical dance is difficult. The first, undoubtedly, is the lack of language support, the French language. Secondly, the dance is the art of movement, and as such, learning vocabulary involves the presence of pictures, models. The WebQuest as a teaching option is able to meet these needs and provide a tool that allows a domain receptive and productive technical vocabulary of academic dance. With this proposal for work in the classroom, students personal experience conflicts, become aware of them and take personal solutions critically. Through the WebQuest The Vocabulary of Classical Dance, students process information favoring the benefits we provide networking tools, illustrated with iconographic and visual elements, thus mitigating the problems that arise in the study of terminology classical dance.